What number is 100 times as great as 0.3

Answers

Answer 1
Answer: 100 times as great as 0.3 =
100 x 0.3 which equals 30
answer = 30
Answer 2
Answer: You do 100 times .3 and that equals 30. 

Related Questions

Can someone help me solve this please?
)Figure XYZ is reflected about the y-axis to obtain figure X’Y’Z’: A coordinate plane is shown Triangle XYZ has vertices X at 5 comma negative 4, vertex Y at 2 comma negative 4, and Z at 4 comma negative 1. Triangle X prime Y prime Z prime has vertices at X prime negative 5 comma negative 4, Y prime at negative 2 comma negative 4, and Z prime at negative 4 comma negative 1. Which statement best describes the relationship between the two figures? Figure XYZ is bigger than figure X’Y’Z’. Figure XYZ is congruent to figure X’Y’Z’. The measure of angle R is equal to the measure of angle S’. The measure of angle R is equal to the measure of angle T’.
Use rounding or compatible numbers to estimate the sum 302+412
What is the type of fee charged for withdrawing money from a CD before thedate of maturation?OOOA. FDIC feeB. Early redemption feeC. Liquidity feeSUBMITPREVIOUS
7/9 divided by 2 13/18

Janie was given (-2,3) as the endpoint of a line segment and (1,0) as its midpoint. Which ordered pair should Janie choose as the other endpoint?A. (-1/2, 3/2)
B. (1/2, 1/2)
C. (-5,6)
D. (4,-3)

Answers

Answer:

The other endpoint

(x_(2) , y_(2)) is (4,-3)

Step-by-step explanation:

Given

Point 1 (-2,3)

Midpoint = (1,0)

We're to calculate the other end point.

To solve this, we'll make use of the formula of midpoints of line

Given that two lines of coordinates P(x_(1) ,y_(1) ) and Q(x_(2) ,y_(2) )

(m_(1),m_(2)) = (((x_(1) + x_(2) ))/(2) ,((y_(1) + y_(2) ))/(2))\nWhere\nm_(1) = ((x_(1) + x_(2) ))/(2) \nand\nm_(2) = ((y_(1) + y_(2) ))/(2))\n

From the question, we have

m_(1) = 1\nm_(2) = 0\nx_(1) = -2\ny_(1) = 3\n

Calculating x_(2)...

From m_(1) = ((x_(1) + x_(2) ))/(2)

By Substitution, we have

1 = (-2+x_(2) )/(2) \n2 = -2+x_(2)\n2 + 2 = x_(2)\n x_(2) = 4

Calculating y_(2)...

From m_(2) = ((y_(1) + y_(2) ))/(2)

By Substitution, we have

0 = (3+y_(2) )/(2) \n0 = 3+y_(2)\n0 - 3 = y_(2)\n y_(2) = -3

Hence, the other endpoint

(x_(2) , y_(2)) is (4,-3)

(-2+x)/(2)=1(3+y)/(2) =0x = 4 ∧y = -3
R: D (4, -3)

Solve for x in the equation x ^2- 8 x + 41 = 0

Answers

Answer:

Two solutions were found :

x =(8-√-100)/2=4-5i= 4.0000-5.0000i

x =(8+√-100)/2=4+5i= 4.0000+5.0000i

Step-by-step explanation:

Step  1  :

Trying to factor by splitting the middle term

1.1     Factoring  x2-8x+41

The first term is,  x2  its coefficient is  1 .

The middle term is,  -8x  its coefficient is  -8 .

The last term, "the constant", is  +41

Step-1 : Multiply the coefficient of the first term by the constant   1 • 41 = 41

Step-2 : Find two factors of  41  whose sum equals the coefficient of the middle term, which is   -8 .

     -41    +    -1    =    -42

     -1    +    -41    =    -42

     1    +    41    =    42

     41    +    1    =    42

Observation : No two such factors can be found !!

Conclusion : Trinomial can not be factored

Equation at the end of step  1  :

 x2 - 8x + 41  = 0

Step  2  :

Parabola, Finding the Vertex :

2.1      Find the Vertex of   y = x2-8x+41

Parabolas have a highest or a lowest point called the Vertex .   Our parabola opens up and accordingly has a lowest point (AKA absolute minimum) .   We know this even before plotting  "y"  because the coefficient of the first term, 1 , is positive (greater than zero).

Each parabola has a vertical line of symmetry that passes through its vertex. Because of this symmetry, the line of symmetry would, for example, pass through the midpoint of the two  x -intercepts (roots or solutions) of the parabola. That is, if the parabola has indeed two real solutions.

Parabolas can model many real life situations, such as the height above ground, of an object thrown upward, after some period of time. The vertex of the parabola can provide us with information, such as the maximum height that object, thrown upwards, can reach. For this reason we want to be able to find the coordinates of the vertex.

For any parabola,Ax2+Bx+C,the  x -coordinate of the vertex is given by  -B/(2A) . In our case the  x  coordinate is   4.0000  

Plugging into the parabola formula   4.0000  for  x  we can calculate the  y -coordinate :

 y = 1.0 * 4.00 * 4.00 - 8.0 * 4.00 + 41.0

or   y = 25.000

Parabola, Graphing Vertex and X-Intercepts :

Root plot for :  y = x2-8x+41

Axis of Symmetry (dashed)  {x}={ 4.00}

Vertex at  {x,y} = { 4.00,25.00}

Function has no real roots

Solve Quadratic Equation by Completing The Square

2.2     Solving   x2-8x+41 = 0 by Completing The Square .

Subtract  41  from both side of the equation :

  x2-8x = -41

Now the clever bit: Take the coefficient of  x , which is  8 , divide by two, giving  4 , and finally square it giving  16

Add  16  to both sides of the equation :

 On the right hand side we have :

  -41  +  16    or,  (-41/1)+(16/1)

 The common denominator of the two fractions is  1   Adding  (-41/1)+(16/1)  gives  -25/1

 So adding to both sides we finally get :

  x2-8x+16 = -25

Adding  16  has completed the left hand side into a perfect square :

  x2-8x+16  =

  (x-4) • (x-4)  =

 (x-4)2

Things which are equal to the same thing are also equal to one another. Since

  x2-8x+16 = -25 and

  x2-8x+16 = (x-4)2

then, according to the law of transitivity,

  (x-4)2 = -25

We'll refer to this Equation as  Eq. #2.2.1  

The Square Root Principle says that When two things are equal, their square roots are equal.

Note that the square root of

  (x-4)2   is

  (x-4)2/2 =

 (x-4)1 =

  x-4

Now, applying the Square Root Principle to  Eq. #2.2.1  we get:

  x-4 = √ -25

Add  4  to both sides to obtain:

  x = 4 + √ -25

In Math,  i  is called the imaginary unit. It satisfies   i2  =-1. Both   i   and   -i   are the square roots of   -1

Since a square root has two values, one positive and the other negative

  x2 - 8x + 41 = 0

  has two solutions:

 x = 4 + √ 25 •  i

  or

 x = 4 - √ 25 •  i

Solve Quadratic Equation using the Quadratic Formula

2.3     Solving    x2-8x+41 = 0 by the Quadratic Formula .

According to the Quadratic Formula,  x  , the solution for   Ax2+Bx+C  = 0  , where  A, B  and  C  are numbers, often called coefficients, is given by        

           - B  ±  √ B2-4AC

 x =   ————————

                     2A

 In our case,  A   =     1

                     B   =    -8

                     C   =   41

Accordingly,  B2  -  4AC   =

                    64 - 164 =

                    -100

Applying the quadratic formula :

              8 ± √ -100

  x  =    —————

                   2

In the set of real numbers, negative numbers do not have square roots. A new set of numbers, called complex, was invented so that negative numbers would have a square root. These numbers are written  (a+b*i)

Both   i   and   -i   are the square roots of minus 1

Accordingly,√ -100  =

                   √ 100 • (-1)  =

                   √ 100  • √ -1   =

                   ±  √ 100  • i

Can  √ 100 be simplified ?

Yes!   The prime factorization of  100   is

  2•2•5•5

To be able to remove something from under the radical, there have to be  2  instances of it (because we are taking a square i.e. second root).

√ 100   =  √ 2•2•5•5   =2•5•√ 1   =

               ±  10 • √ 1   =

               ±  10

So now we are looking at:

          x  =  ( 8 ± 10i ) / 2

Two imaginary solutions :

x =(8+√-100)/2=4+5i= 4.0000+5.0000i

 or:

x =(8-√-100)/2=4-5i= 4.0000-5.0000i

Two solutions were found :

x =(8-√-100)/2=4-5i= 4.0000-5.0000i

x =(8+√-100)/2=4+5i= 4.0000+5.0000i

Processing ends successfully

plz mark me as brainliest :)

Answer:

x =  4 - 5i,  4 + 5i.

Step-by-step explanation:

This won't factor so we can use competing the square:

x^2 - 8x + 41 = 0

x^2 - 8 x = -41

(x - 4)^2 - 16 = -41

(x - 4)^2 = -25         Taking square roots:

x - 4 = +/-5i

x =  4 - 5i, 4 + 5i.

What is one solution of the following system?{2y-2x=12}
{x^2+y^2=36}
A.)(-6,0)
B.)(-2,4)
C.)(0,-6)
D.)(4,-2)

Answers

Answer:

(-6, 0)

Step-by-step explanation:

Check out A):  (-6,0).  This satisfies 2y-2x=12:  2(0) - 2(-6) = 12, and also satisfies x^2+y^2=36:  (-6)^2 + 0^2 = 36.  (-6, 0) is therefore a solution of the given system.

Is the equation xº -5x + 6 = 0 quadratic in form?
Explain why or why not.

Answers

Answer:

Step-by-step explanation:

No because the quadratic form is ax^2 + bx + c = 0. The equation,  xº -5x + 6 = 0, is not in quadratic form because xº is not x^2, yet the rest of the equation follows the quadratic equation template.

How do i make 45/150 a fraction and a decimal

Answers

0.3 is the decimal of 45/150 

To change fraction into decimal you need the divide the denominator by the numerator.
So  150 divided by 45 is 0.3.
you would divide 45 divided by 150 to get 0.3

Inequalities on the Number LineStacie trying to find the temp. <,>,=,≤,
is the number line open or closed
( draw a number line).

Answers

The number line is a closed circle because the circle at the ends are not shaded in. A closed circle to the right means greater than. (>) A closed circle to the left means less than. (<)